Das deutsche Russlandgeschäft im Schatten der Krise: Gefährliche Abhängigkeiten? - Claus-Friedrich Laaser; Klaus Schrader (Wirtschaftsdienst, 2014)
Die deutsch-russischen Wirtschaftsbeziehungen haben sich seit den 1990er Jahren fast unbemerkt von der (medialen) Öffentlichkeit positiv weiterentwickelt. Russland wurde zwar als G8-Mitglied und eines der wichtigen Schwellenländer der BRIC-Gruppe wahrgenommen, mehr Aufmerksamkeit genoss allerdings China. Die Bedeutung Russlands für die deutsche Wirtschaft ist - abgesehen vom Erdgasimport und dem damit untrennbar verbundenen Staatsunternehmen Gazprom - dagegen im Verborgenen geblieben. – – In view of the Russian annexation of Crimea and its ongoing efforts to destabilise Ukraine, political decision-makers in the EU and the US are considering economic sanctions against Russia. The article analyses whether the German economy would be affected by restrictions on trade and investment relations. As a result, German exporters would suffer from restrictions on business relations with Russia, but they would be able to compensate for possible losses. Russian gas export interruptions, however, would be a more severe problem. Due to Russia's dependence on revenues from the export of natural resources as well as on technology imports from Western countries, the Russian economy would be hit particularly hard.
Keywords: F13; F14; F51; 330; Internationale Wirtschaftsbeziehungen; Außenhandelsstruktur; Erdgas; Außenhandel; Kapitalmobilität; Deutschland; Russland